Incremento de espécies arbóreas com potencialidade de uso múltiplo - Souza, Alan Pena de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
The extension of the widespread drought period to the coming decades, coupled with the sharp increase in the number of fires and illegal extraction, can cause changes in the dynamics of the Amazon rainforest. Uncertainties in predicting the responses of this ecosystem to changes in the abiotic and biotic environment arise due to the high diversity of tree species. The aim of this study was to investigate the monthly increase in trunk diameter of six tree species distributed in 43 trees, as well as to determine the effect of climate factors and the presence of neighboring trees (index of neighborhood crowding) on the ecophysiology of trees in a plateau at a pristine terra firme rainforest in central Amazonia. The 2019 accumulated rainfall was 2787.8 mm, with a minimum accumulation of 86.45 mm in July and maximum in May (416.8 mm), the average relative humidity (RH) was 82.51%, varying between 50.13 to 97.59%. The average temperature was 26.16 ºC, with a minimum of 23.58 ºC and a maximum of 29.95 ºC. Photosynthetically active radiation (PAR) averaged 26.45 mol m-2 day–1, with the maximum in march 2019, 32.9 mol m–2 day–1 and the minimum 18.5 mol m-2 day–1 in May 2019. The average vapor pressure deficit (VPD) was 16.77 hPa. The average reference evapotranspiration (EVT) was 116.64 mm month–1. The soil water content (SWC) with an average of 44.5% (v/v) and a maximum of 47% (v/v) and a minimum of 42.4% (v/v). The average monthly growth in diameter (MGD) was 0.10 mm month–1. P. macrophylla (0.15 mm month–1) and M. guianensis (0.13 mm month–1) obtained the highest MGD, while the lowest MGD was observed in the species G. argenteum and I. laurina both with 0.07 mm month–1, with the species P. decandrum and P. hebetatum showing similar values. The mean diameter of the breast height (DBH) was (24 cm), while the mean height was (23 m). In the trees with the highest height and crown, the highest MGD was observed. The functional traits of shell thickness, crown diameter, height and DBH were more closely related to the MGD. The results suggest that taller individuals tend to tolerate more agglomeration of neighboring trees, as well as species with denser woods, such as P. macrophylla, G. argenteum and M. guianensis, since these species have individuals that reach the forest canopy. Therefore, the results found in this work, highlight that the differences in the abiotic and biotic environment, shape the dynamics of the community in tropical forests.
Increment of tree species with multiple use potentiality
Keywords: Ecofisiologia de árvores